What is Artificial General Intelligence and Why Could It Be a Threat as Serious as Climate Change?: An Urgent Call for Medical Education - Kıyak, Yavuz Selim (European Journal of Therapeutics, 2024)
This article not only explains Artificial General Intelligence (AGI) and Artificial Superintelligence (ASI) concisely in a manner that improves understanding among medical educators and professionals, but also contrasts the emphasis on climate change in medical education with the comparatively less attention paid to the threat of AGI and ASI. Awareness is called for about this technology, which could potentially lead to a prosperous age or the extinction of humanity.